Inequality and Economic Growth: The Perspective of the New Growth Theories - Aghion, Philippe; Caroli, Eve; García-Peñalosa, Cecilia (Journal of Economic Literature, 1999)
We analyze the relationship between inequality and economic growth from two directions. The first part of the survey examines the effect of inequality on growth, showing that when capital markets are imperfect, there is not necessarily a trade-off between equity and efficiency. It therefore provides an explanation for two recent empirical findings, namely, the negative impact of inequality and the positive effect of redistribution upon growth. The second part analyzes several mechanisms whereby growth may increase wage inequality, both across and within education cohorts. Technical change, and in particular the implementation of “General Purpose Technologies,” stands as a crucial factor in explaining the recent upsurge in wage inequality.